Premature Indonesia Support Group in Health Communication: Efforts to Prevent Retinopathy of Prematurity in Indonesia - Rani Sukma Ayu Suteja; Umar Umar; Wibowo Nimas Safira Widhiasti; Ramadhiansyah Dimas; Aji Angga Prawadika (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
This study aimed to discuss the role of the Premature Indonesia support group in health communication as an effort to prevent retinopathy of prematurity (ROP) in Indonesia. ROP is an eye developmental disorder due to premature birth, which results in a child’s permanent blindness. The awareness about the risk of ROP is still very low so health communication efforts are currently necessary. This study was conducted using a qualitative research approach with in-depth interviews as the primary data. The secondary data were collected through literature study, observation, and researcher’s experience. The results showed that Premature Indonesia’s health communication efforts were carried out through several stages namely analyzing main problems, selecting credible and experienced educators, using social media as the main communication medium, and formulating and delivering explicit health information messages. Through these health communication efforts, the Premature Indonesia support group could increase health awareness and the risk of ROP in premature babies along with its prevention efforts. Keywords: health communication, public health, retinopathy of prematurity, prematurity, child blindness, social support.